The Community Role in the Implementation of Coronavirus Disease-19 Control Policies in Indonesia - Mujiati Mujiati; Mimi Sumiarsih; Aryani Pujianti (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2022)
Background: The success of COVID-19 control in Indonesia comes to place with active community participation. Community's role in supporting the successful implementation of COVID-19 policy is critical to investigate. This study, therefore, aimed to determine community’s role in supporting the successful implementation of COVID-19 control policies.Method: This study is exploratory research with a cross-sectional approach. Seven Indonesian regencies as research locations were selected purposively. Quantitative data were collected from 2,010 positive-COVID-19 patients and their close contacts through a standardized self-administered questionnaire. In-depth interviews were employed with 79 health center officers. Content analysis was used to analyze the qualitative data, and descriptive analysis was for the quantitative data. Results: This study had a relatively balanced gender distribution. There were 26.9% at age of 6-19 years, and 80.9% were in close contact with COVID-19 patients. Most respondents were from primary health care centers, had a bachelor's degree, and had worked for less than five years. Their adherence to health protocols was lower than the group that was not exposed to COVID-19. Most respondents followed health protocols such as hygiene (92.9 %) and cough etiquette (91.5 %). However, COVID-19 quarantine compliance was still low (38.2%), and 90.8% of respondents mostly practiced self-isolation at home. COVID-19 control strategies in each region quite varied. A lack of public awareness and education, flexibility in policy implementation, and a poor reward and punishment system were barriers to COVID-19 control. The community's role in supporting COVID-19 control policies includes helping to communicate COVID-19 risks, assisting healthcare centers in monitoring COVID-19 self-isolation, providing and operating integrated isolation shelters for confirmed cases, and participating as a case tracer.